Dual porosity 3D printed scaffolds to modulate the immune response - Oliveira, Maria Carlos (2020)
Besides the advanced knowledge on the fabrication of complex implant biomaterials, modulating the host response is still an unmet challenge in medical applications. The main regulators of this response are the macrophages that can polarize from a pro-inflammatory (M1) phenotype to an anti-inflammatory phenotype (M2) and affect the path of the immune response. Nowadays, strategies to influence macrophage activation for regenerative medicine are being explored to better understand their complex role. Ideally, this modulation would be achieved by altering the physicochemical properties (e.g. stiffness, porosity, topography) of a biomaterial without the addition of exogenous cytokines, growth factors or complicated cell therapies. Thus, this work aimed to create 3D-printed scaffolds with dual porosity and controllable topography, that can tune the foreign body response, fabricated from additive manufacturing and Thermally Inducible Phase Separation (TIPS). Two polymers of Poly(ε-caprolactone-co-lactide) (PCLLA) with different crystallinity were used to fabricate the scaffolds and showed higher porosity and surface roughness than Fused Modelling Deposition (FDM) scaffolds. 3D-TIPS scaffolds, that were rougher and more porous, showed higher cell adhesion and decrease of pro-inflammatory cytokine, TNF-α, comparing to FDM scaffolds. From the in vivo results, scaffolds from the amorphous PCLLA composition showed greater degradation than the more crystalline one, resulting in denser fibrous capsule around the biomaterial. 3D-TIPS scaffolds also showed more cell infiltration inside the fibers suggesting interconnected pores, but FDM scaffolds showed great capacity for cell infiltration by its porosity on the z-axis on the more crystalline polymer. Together, these data indicate a great potential for 3D-TIPS scaffolds to supress pro-inflammatory phenotype comparing with FDM, by increased roughness and porosity.